Implementation of Life Skills in Order to Add Family Income and Contributions to Empowerment of Women - Jalius, Jalius; Sunarti, Vevi; Azizah, Zahratul; Gusmanti, Reza (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
Life skills education is a valuable and strategic investment in producing skilled and skilled Indonesian people in various fields according to the needs of the community and the world of work. This means that life skills are given to all elements of society, especially for women. Women as someone who has an important role in the family is the key to success in the existence of his family. Life skills education is provided in order to help increase family income, which in this case contributes to women's empowerment. Padang State University as one of the higher education institutions facilitates community service. The focus of community service that the writer adopts here is the empowerment of women through the provision of life skills in order to help increase family income. This service was carried out in Nagari Siguntur, Pesisir Selatan Regency. The number of subjects (training participants) is 15 women. The method used is lectures, workshops and training. Data collection techniques are observation (assessment process) and interviews. The data analysis technique used is descriptive analysis. The results of the implementation of the community empowerment program showed that (1) the number of participants who actively participated in women's empowerment activities through the provision of life skills was 15 people, (2) the training participants had knowledge and skills in making bross, and arranging flowers from used cloth, (3) the formation of a small-scale bross production group as souvenirs for parties and cloth flower displays.Keywords: Women's Empowerment, Life Skills, Family Income